2022
DOI: 10.1016/j.jadohealth.2021.12.022
|View full text |Cite
|
Sign up to set email alerts
|

College Student-athletes' COVID-19 Worry and Psychological Distress Differed by Gender, Race, and Exposure to COVID-19–related Events

Abstract: Purpose The purpose of this study was to determine the prevalence of National Collegiate Athletic Association (NCAA) student-athletes’ exposure to COVID-19–related events (e.g., canceled season, diagnosed with COVID) and their psychological distress in April/May 2020. Methods The link to the online survey was emailed to NCAA student-athletes by the NCAA Student Athlete Advisory Council and the athletic departments of 80 NCAA institutions. In April–May of 2020, student-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Exploratory factor analysis and reliability of CAS-EA Previous studies have reported isolation, training interruption, loss of income, and career as anxiety factors during the COVID-19 pandemic [12]. Furthermore, they reported that the main sources of anxiety at more than one year after release from confinement were related to the future of the sport and their sports careers [13].…”
Section: Discussionmentioning
confidence: 99%
“…Exploratory factor analysis and reliability of CAS-EA Previous studies have reported isolation, training interruption, loss of income, and career as anxiety factors during the COVID-19 pandemic [12]. Furthermore, they reported that the main sources of anxiety at more than one year after release from confinement were related to the future of the sport and their sports careers [13].…”
Section: Discussionmentioning
confidence: 99%
“…After receiving approval through from the university institutional review board (IRB), we contacted NCAA Division I, Division II, and Division III athletic departments to solicit their involvement in the study. Over 80 athletic departments agreed to participate and distributed information about our study to their student athletes; data used in this study were extracted from a larger study on NCAA student athletes’ psychological well-being during the COVID-19 pandemic and have not been reported elsewhere (e.g., Moore et al, 2022). Data collection spanned from March 2020 to April 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have examined the pandemic's impact on economic aspects, regular daily routines and functioning, academic functioning, and physical and mental health, as well as the lack of academic sporting activities [55][56][57]. The pandemic's negative effects on college students may vary according to students' socioeconomic status.…”
Section: Emergency Remote Education and Potential Impactmentioning
confidence: 99%